Produksi Diskursif Rasa Aman: Analisis Relasi Kuasa-Pengetahuan dalam Kebijakan Kriminalitas Kemenko Polkam - Asmoro Aji; Arizal Mutahir; Eros Shidqy Putra (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2026)
This study aims to analyze the discursive construction of the sense of safety through power/knowledge relations in the crime control policies of Indonesia’s Coordinating Ministry for Political and Security Affairs. The study employs a qualitative approach using Michel Foucault’s Critical Discourse Analysis. The data consist of the Ministry’s Performance Reports, crime statistics published by the Indonesian National Police, and survey indicators issued by Statistics Indonesia (BPS). The analysis is conducted through archaeological and genealogical approaches to examine how the sense of safety is constituted both as an object of knowledge and as an instrument of governmentality. The findings demonstrate that the sense of safety indicator functions not merely as a measurement tool but also as a discursive construct that legitimizes public policy and produces a regime of truth. Consequently, crime control policy operates as a mechanism of power/knowledge that shapes the ways in which the state governs the population while simultaneously influencing public understandings of security.